catena-Poly[[silver(I)-μ-4,4′-bipyridine-κ2N:N′] 4-[2-(4-carboxyphenyl)-1,1,1,3,3,3-hexafluoropropan-2-yl]benzoate] - Xiu-Juan Jiang (Acta Crystallographica Section E, 2012)
Assembly of the flexible dicarboxylic ligand 4-[2-(4-carboxyphenyl)-1,1,1,3,3,3-hexafluoropropan-2-yl]benzoate and 4,4′-bipyridine as co-ligand with AgI ions resulted in the formation of the polymeric title compound, {[Ag(C10H8N2)](C17H9F6O4)}n, in which the metal atoms are bridged by the 4,4′-bipyridine ligands, generating cationic chains extending along [010]. The dihedral angles between the benzene rings in the anion and the pyridine rings in the cation are 72.42 (9) and 9.36 (10)°, respectively. The molecular conformation of the anion is stabilized by intramolecular C—H...F hydrogen bonds. In the crystal, the anions interact with the cationic chains via C—H...O hydrogen bonds, forming layers parallel to (001), in which weak π–π stacking interactions [centroid–centroid distances = 3.975 (3)–4.047 (3) Å] involving the pyridine rings of adjacent 4,4′-bipyridine ligands are present. The planes are further assembled into a three-dimensional network by O—H...O hydrogen bonds.